A review – exploring the performance degradation mechanisms of LiCoO2 cathodes at high voltage conditions and some optimizing strategies. (22nd July 2022) - Wang, Chenyu; Weng, Jingzheng; Wu, Shuru; Zhang, Xian; Tong, Qingsong; Zhu, Mengqi
Abstract : The factors affecting the capacity degradation of lithium-ion batteries with LiCoO2 as the cathode material at high voltage are discussed, and then doping and surface coating strategies are proposed as corresponding solutions. Abstract : A high voltage enables batteries to have a larger capacity, which is indispensable for the development of new energy materials. However, the emergence of issues relating to stability and performance fading caused by high voltage has critically impeded the practical application of such materials. This review condenses studies of performance fading mechanisms and corresponding solution strategies involving LiCoO2 at high voltage. First, it introduces the definition of LiCoO2 and outlines the urgent demand for higher-capacity LiCoO2, which requires LiCoO2 to endure higher charging and discharging voltages. Afterwards, due to the above-mentioned demand, various problems generated at high voltage are discussed, which are essential to be solved. Moreover, corresponding improvement strategies involve two aspects: doping, affecting the phase structure; and surface coating, affecting interfaces. Finally, it proposes some conclusions and perspectives for gaining a better understanding of LiCoO2 when applied to high-voltage LIBs.